Svinarka i pastukh - Pyriev, Ivan (Soviet Union, 1941)
Musical comedy. Love story of a Russian milkmaid and a Dagestani shepherd who meet and fell in love at the Agricultural Exhibitions in Moscow. After some required comic complications, the two exemplary workers unite.
Keywords: Fiction films